ChemInform Abstract: Domino Inverse Electron‐Demand Diels—Alder/Cyclopropanation Reaction of Diazines Catalyzed by a Bidentate Lewis Acid. Issue 20 (25th April 2013) - Kessler, Simon N.; Neuburger, Markus; Wegner, Hermann A.
Abstract The coupling of phthalazines with electron‐rich furans in the presence of a Lewis acid is found to provide a new and stereoselective approach to benzonorcaradienes.